Change in interfacial properties of milk fat globules by homogenization and thermal processing plays a key role in their in vitro gastrointestinal digestion. (November 2019) - Zhao, Lili; Du, Min; Mao, Xueying
Abstract: The effects of homogenization, homogenization plus thermal processing including high temperature short time (HHTST) or ultra-high temperature (HUHT) treatment on digestion and interfacial properties of milk fat globules during simulated gastrointestinal digestion were investigated. Compared to raw milk fat globules, homogenization and thermal processing increased the initial digestion rate of milk fat globules. Homogenization increased the release of middle- and long-chain fatty acids, HHTST increased the release of unsaturated fatty acids, and HUHT increased the release of all types of fatty acids under gastrointestinal digestion. After homogenization, milk proteins (caseins and whey proteins) increased but glycosylated molecules decreased, both of which were at the surface of milk fat globules. The amount of glycosylated molecules at the surface of HHTST milk fat globules and the amount of denatured milk proteins at the surface of HUHT milk fat globules were higher than those of homogenized milk fat globules. During gastrointestinal digestion, fat globules in HHTST milk possessed higher amount of glycosylated molecules and more integrated phospholipid layers, and HUHT milk fat globules had more filamentous phospholipid layers, and less integrated phospholipid layers and glycosylated molecules than those of homogenized milk fat globules. Therefore, the changes in composition and microstructure of glycosylated molecules and phospholipid layers at the surface of milk fat globules induced by homogenization and thermal processing might contribute to the digestion difference of milk fat globules. Graphical abstract: Homogenization and thermal processing changed the size and interfacial compositions of milk fat globules. Homogenization increased milk proteins (caseins and whey proteins) but decreased glycosylated molecules. Homogenization plus thermal processing including high temperature short time (Homogenization + HTST, HHTST) or ultra-high temperature (Homogenization + HUHT, HUHT) increased glycosylated molecules and denatured milk proteins. During gastric digestion, phospholipid layers of smaller natural fat globule in processed milk were exposed, but newly formed milk fat globule that was coated or embedded with milk proteins was hydrolyzed by lipase after pepsin hydrolysis of interfacial protein. During intestinal digestion, phospholipid layer was replaced by bile salts and milk fat globules were hydrolyzed by lipase. The different changes of milk fat globules caused by homogenization, HHTST and HUHT ultimately contributed to the release of free fatty acids and digestion rate of milk fat globules.Image 1 Highlights: Dairy processing changed the interfacial properties of milk fat globules. Dairy processing affected the digestion of milk fat globules. Processed milk fat globules were more readily digestible than raw milk fat globules.